1996
DOI: 10.1111/j.1476-5381.1996.tb15533.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic inhibitors of endopeptidase EC 3.4.24.15: potency and stability in vitro and in vivo

Abstract: 1 The role of the metalloendopeptidase EC 3.4.24.15 (EP 24.15) in peptide metabolism in vivo is unknown, in part reflecting the lack of a stable enzyme inhibitor. The most commonly used inhibitor, N-[1-(R,S)-carboxy-3-phenylpropyl]-Ala-Ala-Tyr-p-aminobenzoate (cFP-AAY-pAB, K,= 16 nM), although selective in vitro, is rapidly degraded in the circulation to cFP-Ala-Ala, an angiotensin converting enzyme (ACE) inhibitor. This metabolite is thought to be generated by neutral endopeptidase (NEP; EC 3.4.24.11), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The treatments and P values are the same as for Figure 2. rabbits. However, these effects are entirely attributable to inhibition of ACE by the metabolite cFP-AA (Telford et al, 1995;Lew et al, 1996). Similar observations have been made in anaesthetized rats in which the phenylalanine substituted analogue cFP-AAF-pAB was used (Yang et al, 1994).…”
Section: Effects Of Inhibition Of Ep 2415supporting
confidence: 67%
See 2 more Smart Citations
“…The treatments and P values are the same as for Figure 2. rabbits. However, these effects are entirely attributable to inhibition of ACE by the metabolite cFP-AA (Telford et al, 1995;Lew et al, 1996). Similar observations have been made in anaesthetized rats in which the phenylalanine substituted analogue cFP-AAF-pAB was used (Yang et al, 1994).…”
Section: Effects Of Inhibition Of Ep 2415supporting
confidence: 67%
“…Although both cFP-AAY-pAB and cFP-AAF-pAB have low affinity for EP 24.11, they can inhibit this enzyme at higher concentrations (Ki values of 35 and 17 gM respectively). We have found previous in studies in conscious rabbits that a bolus dose of cFP-AAY-pAB of 5 mg kg-1, although rapidly cleared from the circulation (100 fold lower levels in 5 min), results in peak blood levels over 100 gM (Lew et al, 1996), which would be expected to inhibit EP 24.11. We chose to use a dose of 0.1 mg kg-' Hoe 140 in our subsequent experiment, and unexpectedly found that it increased Na+ excretion.…”
Section: Effects Of Inhibition Of Ep 2415mentioning
confidence: 95%
See 1 more Smart Citation
“…Biological stability was enhanced 20-fold (Ser) and 10-fold (Val, Leu) in comparison with cFP. However, the Val-substituted analogue was cleared from the circulation of conscious rabbits at the same rate as cFP and, like cFP, blunted the pressor response to angiotensin I, again indicative of ACE inhibition [13].…”
Section: Discussionmentioning
confidence: 90%
“…l K i (1j[S]\K m ). The K m had been determined as 19.8 µM by a Lineweaver-Burk analysis of initial velocities measured in triplicate at a range of QFS concentrations (1.1-140 mM) [13]. ACE (human plasma) was assayed by using the fluorimetric ACE method, as described by Friedland and Silverstein [14], which measures the degradation of hippuryl-His-Leu.…”
Section: Inhibition Studiesmentioning
confidence: 99%